2023
DOI: 10.1021/acs.chemmater.3c01260
|View full text |Cite
|
Sign up to set email alerts
|

From Well-Defined Clusters to Functional Materials: Molecular Engineering of Amorphous Molybdenum Sulfides for Hydrogen Evolution Electrocatalysis

Francisco Gonell,
Miriam Rodenes,
Santiago Martín
et al.

Abstract: Developing precious-metal-free electrocatalysts for the hydrogen evolution reaction (HER) is crucial to establishing H 2 produced from renewable energy sources as an alternative energy carrier to fossil fuels. Amorphous molybdenum sulfide-based materials are promising candidates that provide highly active HER electrocatalysts by introducing active sites at both the edge positions and the typically inactive basal planes. Herein, we report an innovative bottom-up synthesis of amorphous molybdenum sulfides using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…Despite the great promise of a-MoS x , the origin of its high catalytic activity, as well as the structure–activity relations and surface spatial heterogeneity of a-MoS x , is underexplored. , In fact, the exact structure of a-MoS x and therefore the possible bonding environments of the S atomsis still under debate . Experimental and theoretical studies have identified that the HER activity of a-MoS x samples is intimately linked to the S types present, making this information vital to aid in the systematic design of high-performance a-MoS x catalysts. Further, there is a consensus within the literature that thicker a-MoS x films show higher activity; however, such measurements are taken macroscopically only and have not been fully rationalized. , …”
Section: Introductionmentioning
confidence: 99%
“…Despite the great promise of a-MoS x , the origin of its high catalytic activity, as well as the structure–activity relations and surface spatial heterogeneity of a-MoS x , is underexplored. , In fact, the exact structure of a-MoS x and therefore the possible bonding environments of the S atomsis still under debate . Experimental and theoretical studies have identified that the HER activity of a-MoS x samples is intimately linked to the S types present, making this information vital to aid in the systematic design of high-performance a-MoS x catalysts. Further, there is a consensus within the literature that thicker a-MoS x films show higher activity; however, such measurements are taken macroscopically only and have not been fully rationalized. , …”
Section: Introductionmentioning
confidence: 99%